Characterizing the multiple roles of FGF‐2 in SOD1G93A ALS mice in vivo and in vitro. Issue 5 (28th October 2018) - Kefalakes, Ekaterini; Böselt, Sebastian; Sarikidi, Anastasia; Ettcheto, Miren; Bursch, Franziska; Naujock, Maximilian; Stanslowsky, Nancy; Schmuck, Martin; Barenys, Marta; Wegner, Florian; Grothe, Claudia; Petri, Susanne
Abstract: We have previously shown that knockout of fibroblast growth factor‐2 (FGF‐2) and potential compensatory effects of other growth factors result in amelioration of disease symptoms in a transgenic mouse model of amyotrophic lateral sclerosis (ALS). ALS is a rapidly progressive neurological disorder leading to degeneration of cortical, brain stem, and spinal motor neurons followed by subsequent denervation and muscle wasting. Mutations in the superoxide dismutase 1 (SOD1) gene are responsible for approximately 20% of familial ALS cases and SOD1 mutant mice still are among the models best mimicking clinical and neuropathological characteristics of ALS. The aim of the present study was a thorough characterization of FGF‐2 and other growth factors and signaling effectors in vivo in the SOD1 G93A mouse model. We observed tissue‐specific opposing gene regulation of FGF‐2 and overall dysregulation of other growth factors, which in the gastrocnemius muscle was associated with reduced downstream extracellular‐signal‐regulated kinases (ERK) and protein kinase B (AKT) activation. To further investigate whether the effects of FGF‐2 on motor neuron death are mediated by glial cells, astrocytes lacking FGF‐2 were cocultured together with mutant SOD1 G93A motor neurons. FGF‐2 had an impact on motor neuron maturation indicating that astrocytic FGF‐2 affects motor neurons at a developmental stage. Moreover, neuronal gene expression patterns showed FGF‐2‐ and SOD1 G93A ‐dependent changes in ciliary neurotrophic factor, glial‐cell‐line‐derived neurotrophic factor, and ERK2, implying a potential involvement in ALS pathogenesis before the onset of clinical symptoms. Abstract : Characterization of fibroblast growth factor‐2 (FGF‐2) and other growth factors and signaling effectors in vivo and in vitro in the SOD1G93A mouse model. Tissue‐specific opposing gene regulation of FGF‐2 and overall dysregulation of other growth factors were observed, which in the gastrocnemius muscle was associated with reduced downstream‐extracellular‐signal‐regulated kinases (ERK) and protein kinase B (AKT) activation.